Pengaruh Anggaran Belanja Langsung Terhadap Realisasi Anggaran Pada Biro Umum Sekretariat Provinsi Jawa Barat - Hasbi Basith Sukarno (Exchall: Economic Challenge, 2021)
This reseach aimed to find out the influence of direct budget on budget realization in Biro Umum Sekretariat Provinsi Jawa Barat period 2013-2017.The reseach used quantitative descriptive method. The data collection technique used is observation, library study and documentation. The data analysis technique used is a Pearson Product Moment Correlation, coefficient of determination, the simple linear regression,and t test. The results obtained from statistical calculations, obtained the value of the correlation coefficient between the direct budget to budget realization of 0.993. While the regression coefficient value was stated positive so that if the direct budget increases then the budget realization will increase. Determination coefficient value was 0.985 which means the direct budget gives an influence of 98,5% to budget realization.The problems in Biro Umum Sekretariat Provinsi Jawa Barat. Efforts made on this issue are improving the quality and quantity in budget planning so that the process of realization or disbursement of funds does not occur misunderstanding ot late. Keyword : Direct budget, Budget realization